Peranan Raja Faisal Bin Abdul Aziz Al-Saud dalam Mempertahankan Kedaulatan Wilayah Palestina (1930-1975) - Diman, Muhammad Wardiman; Susmihara; Suraya Rasyid; Abu Haif (Rihlah: Jurnal Sejarah dan Kebudayaan, 2024)
This research studies the role of a figure titled "The Role of King Faisal bin Abdul Aziz in Defending the Sovereignty of the Palestinian Territory (1930-1975)". King Faisal is a leader of the State of Saudi Arabia who has made various efforts to liberate Palestine from Jewish occupation. This research includes historical research using heuristics, source criticism, interpretation stages, and historiography. The results of this research showed that the efforts made by King Faisal were in the form of greeting friends from Arab countries to help the Palestinian people in their struggle to defend their territory. Other efforts carry out political diplomacy through various channels, such as the PBB, OKI, Rabitahah al-Alam al-Islami, OPEC (The Organization of the Petroleum Exporting Countries), and making direct contact with organizational leaders in Palestine. Apart from that, King Faisal also provided financial assistance and weapons to Palestine. Therefore, King Faisal is an Islamic figure from Saudi Arabia who has an important role in defending the sovereignty of the Palestinian territory. Keywords : Sovereignty of the Palestinian Territory; King Faisal bin Abdul Aziz Icon of the Liberation of Palestine; 3rd King of Saudi Arabia.